ANALISIS STRATEGI LIKUIDITAS, KUPON, MATURITY DAN RATING OBLIGASI DALAM MENCEGAH GAGAL BAYAR OBLIGASI EVERGRANDE - Dita Ayu Susmita; Mei Habibah Dalimunthe; Gita Islya Asmara; Purnama Ramadani Silalahi; Maryam Batubara (VALUE, 2021)
The second largest property company from the Bamboo Curtain country, the Evergrande Company, experienced an inflated debt worth USD 300 billion which also made it one of the companies that almost defaulted on the bonds issued. It is feared that this phenomenon will have a negative impact on similar companies. The purpose of this study was to analyze the Liquidity Strategy, Coupon, Maturity and Bond Rating in Preventing Default of Evergrande Bonds. Strategy analysis using SWOT analysis. In this study, the researcher used a qualitative descriptive approach. Based on the SWOT analysis, it was found that the financial and non-financial management activities of Evergrande's company were considered bad, thus placing the company in a position of liquidity difficulty, as a result, the company chose to pay off its bonds debt by issuing new bonds until finally the three of red policy emerged, making Evergrande difficult to pay its maturing bonds.